ANALISIS TERHADAP PENERAPAN PERLINDUNGAN KONSUMEN DALAM JUAL BELI ONLINE PADA APLIKASI SHOPEE MENURUT PERSPEKTIF HUKUM ISLAM: Studi Kasus Mahasiswa Institut Agama Islam Az-Zaytun Indonesia Fakultas Syariah - Anisa Alya Madani; Irvan Iswandi (Jurnal Penelitian Multidisiplin Ilmu, 2022)
Shopee Application is one of online shopping platforms which give easiness to its users in carrying out transaction but in its practice also causing problem or disadvantage experienced by the consumer such as the good is not suitable with the picture or the description and high risk of fraud. Related to these loss in Indonesia has been managed concerning the consumer’s rights in The Law Number 8 Year 1999 about Consumer Protection. The problem in this research; how was the analysis on the implementation of consumer protection in online commerce at shopee application and how was the implementation of consumer protection in online commerce at shopee application according to Islamic law perspective. The purpose of this research was to find out the analysis on the implementation of consumer protection in online commerce at shopee application and to find out the implementation of consumer protection in online commerce at shopee application according to Islamic law perspective. This research was a qualitative research. The primary data were collected through online interview using questionnaire spread to students of Shariah Faculty at IAI AL-AZIS to find out the practice of consumer protection implementation in shopee application. The research result concluded that Shopee Application has afforded consumber protection by providing guarantee on the good in the form of shopee guarantee, providing message feature, and giving responsibility to the seller to give proper information to the consumer. Second, the implementation of consumer protection in shopee application has been in line with the Islamic law where the policy concerning consumer protection applied by shopee has been in accordance with the consumer’s right that must be concerned by the businessmen in Islam.